2019
DOI: 10.1002/nop2.427
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices in mental health of health professionals at the end of their curriculum in Burkina Faso: A pilot study

Abstract: Aim To study the knowledge, attitudes and practices regarding mental health amongst health professionals at the end of their curriculum in Burkina Faso. Design A descriptive and cross‐sectional study was adopted. Methods A simple random sampling was used to select 420 health students in Burkina Faso. Self‐administered questionnaires on sociodemographic profile, knowledge, attitudes and practices about mental health were distributed. Results The response rate to the questionnaires was 93%. Our study sample incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…In our study, higher scores of knowledges were associated with being a fourth-year medical student which coincides with the introduction of psychiatry in the curriculum at this level. This is similar to other studies that reported an increase in knowledge of medical students on mental health with age and year of study [30][31][32][33]. It is also found that students in third year onwards are exposed to information on mental health directly or indirectly especially as they begin to interface with the management of patients [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, higher scores of knowledges were associated with being a fourth-year medical student which coincides with the introduction of psychiatry in the curriculum at this level. This is similar to other studies that reported an increase in knowledge of medical students on mental health with age and year of study [30][31][32][33]. It is also found that students in third year onwards are exposed to information on mental health directly or indirectly especially as they begin to interface with the management of patients [31].…”
Section: Discussionsupporting
confidence: 89%
“…This study, as compared to a similar one among university students in Indonesia whose knowledge on mental health was found to be 50.23%, showed that a larger proportion as high as 77.72% was knowledgeable [30]. Lower statistics were also noted in Burkina Faso 2 Unadjusted linear regression analysis displaying factors associated with knowledge, attitudes and perceptions of participants towards mental illness where they reported average knowledge [32]. The difference may be because the study in Indonesia also included non-medical students who are not taught about mental health, despite using similar questions in assessment of knowledge [30].…”
Section: Discussionmentioning
confidence: 56%
“…In addition, this can be explained by the fact that the study population in this study was limited to Burera District while for the other studies, they covered the whole countries. The finding showed that 57.4% have low knowledge in complementary/alternative therapy /psychotherapy and this is associated with education curriculum in school of health sciences as it is in line with the study done by The second objective of this study was to assess the level of attitude among HCPs toward PM+ in Burera District [16]. The findings of this research revealed that 51.8 percent of respondents have positive attitude, which is different from the study conducted in Malaysia where 4.6% of participants had negative attitudes towards CAM [17].…”
Section: Table 2: Multivariate Analysis Of Factors Associated With Pm...supporting
confidence: 71%
“…The questionnaire is based on the World Health Organization (WHO) guide on "Assessment and management of conditions speci cally related to stress: mhGAP Intervention Guide Module" (6) and the study by Sawadogo et al (7). This is a 32-item self-questionnaire: the rst 10 items concern sociodemographic characteristics and general information on psychotrauma.…”
Section: Questionnairementioning
confidence: 99%
“…The next 21 items relate to questions on knowledge of psychotrauma. They were scored according to the methodology used by Sawadogo et al (7). The last item corresponds to the average knowledge score.…”
Section: Questionnairementioning
confidence: 99%